تنظير الإحليل والمثانة خبرة مشفى الأسد الجامعي في اللاذقية ما بين 18/10/2003– 18/4/2004 (Latakia University Journal -Medical Sciences Series, 2019)
تم إجراء تنظير إحليل ومثانة لدى  /139/ مريضا في مشفى الأسد الجامعي في اللاذقية, منهم /107/ ذكور بنسبة 77%, و/32/ إناث بنسبة 23%, لوحظ أن /59/ مريضا بعمر يتخطى 60 عاما بنسبة 57.8%  و35 مريضا بين (60-45)عاما بنسبة 25.2%, و33 مريضا بين (45-30) سنة بنسبة 23.7%, و12 مريضا بين (30-15) سنة بنسبة 8.84% . أكثر الحالات شيوعا لدى الإناث من الفئة العمرية الأولى والثانية والثالثة من (60-15) سنة هي الأمراض التي تقتضي إجراء تركيب أو نزع القثاطر الحالبية تنظيريا, حيث لوحظت لدى عشر مريضات, في حين شخصت أورام المثانة لدى خمس مريضات من الفئة العمرية الرابعة > 60 سنة . أكثر الأمراض شيوعا في الفئة العمرية الأولى للذكور من (30-15) سنة هي تضيق عنق المثانة ودسامات الإحليل الخلفية لدى ثلاثة مرضى لكل منهما, وفي الفئة العمرية الثانية من (45-30) سنة هي تضيق الإحليل حيث شوهد لدى تسعة مرضى, وفي الفئة العمرية الثالثة والرابعة هي فرط تصنع موثي حيث شوهدت لدى /44/ مريضا Cystourethroscopy was performed on 139 patients in Al-Assad University Hospital in Lattakia, /170/ of these patients were males (77%), and /32/ of them were females (32%).it has been noticed that 59 patients were above the age of 60 (57.8%), 35 between (45-60)year with 25.2%, 33 between (30-45) with 23.7%, 12  between (15-30)year with 8.84 %. The most common cases among females of the first, second and third age-groups, which are between 15 and 60 years, was the use of cystourethroscopy for urethral stents in 10 patients, there were bladder tumors in 5     patients of more than 60year group. The most common problems in the case of males of the first age-group (15-30) year were bladder neck contraction and posterior urethral valves in 3 patients of each problem. Nine patients of the second age-group, age between 30 and 45 years old, had urethral strictures. Forty four patients of the third and fourth age-groups had prostatic hyperplasia.